Cell‐Active, Reversible, and Irreversible Covalent Inhibitors That Selectively Target the Catalytic Lysine of BCR‐ABL Kinase. (29th April 2022) - Chen, Peng; Sun, Jie; Zhu, Chengjun; Tang, Guanghui; Wang, Wei; Xu, Manyi; Xiang, Menghua; Zhang, Chong‐Jing; Zhang, Zhi‐Min; Gao, Liqian; Yao, Shao Q.
Abstract: Despite recent interests in developing lysine‐targeting covalent inhibitors, no general approach is available to create such compounds. We report herein a general approach to develop cell‐active covalent inhibitors of protein kinases by targeting the conserved catalytic lysine residue using key SuFEx and salicylaldehyde‐based imine chemistries. We validated the strategy by successfully developing (irreversible and reversible) covalent inhibitors against BCR‐ABL kinase. Our lead compounds showed high levels of selectivity in biochemical assays, exhibited nanomolar potency against endogenous ABL kinase in cellular assays, and were active against most drug‐resistant ABL mutations. Among them, the salicylaldehyde‐containing A5 is the first‐ever reversible covalent ABL inhibitor that possessed time‐dependent ABL inhibition with prolonged residence time and few cellular off‐targets in K562 cells. Bioinformatics further suggested the generality of our strategy against the human kinome. Abstract : A general approach to develop cell‐active covalent inhibitors of protein kinases by targeting the conserved catalytic lysine is reported. Amongst lead compounds, the salicylaldehyde‐containing A5 is the first‐ever reversible covalent ABL inhibitor that possessed time‐dependent nanomolar inhibition against endogenous ABL kinase, with prolonged residence time and few cellular off‐targets.